2021
DOI: 10.1016/j.jsxm.2021.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Female Sexual Dysfunction as Measured by Low Sexual Frequency is Associated with Lower Socioeconomic Status: An Analysis of the National Health and Nutrition Examination Survey (NHANES), 2007-2016

Abstract: Background Female sexual dysfunction (FSD) is a complex disorder of biopsychosocial etiology, and FSD symptoms affect more than 40% of adult women worldwide. Aim In this cross-sectional study, we sought to investigate the association between FSD and socioeconomic status (SES) in a nationally representative female adult population. Methods Economic and sexual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…A nationally representative US study, adjusted for many relationship, health, and socioeconomic factors, reported that, of 7348 women aged 20 to 59 years, the risk of having no sex or sex less than 11 times a year was almost twice as likely among economically poor women (odds ratio, 1.92; 95% confidence interval, 1.21-3.05; P < 0.006). 6 A study of 2109 California insured women aged 40 to 69 years reported that among women making $100,000+ a year, only 8.2% did not have sex in the past year as compared with 49.5% of the women making $40,000 or less ( P < 0.001). 7 It seems remarkable to me that in the socially liberal state of California, almost half of the lower-income middle-aged women reported no sexual activity at all in the past year.…”
Section: Sexual Activity Rates Especially Low Among Low-income Peoplementioning
confidence: 99%
See 1 more Smart Citation
“…A nationally representative US study, adjusted for many relationship, health, and socioeconomic factors, reported that, of 7348 women aged 20 to 59 years, the risk of having no sex or sex less than 11 times a year was almost twice as likely among economically poor women (odds ratio, 1.92; 95% confidence interval, 1.21-3.05; P < 0.006). 6 A study of 2109 California insured women aged 40 to 69 years reported that among women making $100,000+ a year, only 8.2% did not have sex in the past year as compared with 49.5% of the women making $40,000 or less ( P < 0.001). 7 It seems remarkable to me that in the socially liberal state of California, almost half of the lower-income middle-aged women reported no sexual activity at all in the past year.…”
Section: Sexual Activity Rates Especially Low Among Low-income Peoplementioning
confidence: 99%
“…Other studies have reported that rates of partnered sexual activity are especially low among certain populations such as low-income women. A nationally representative US study, adjusted for many relationship, health, and socioeconomic factors, reported that, of 7348 women aged 20 to 59 years, the risk of having no sex or sex less than 11 times a year was almost twice as likely among economically poor women (odds ratio, 1.92; 95% confidence interval, 1.21–3.05; P < 0.006) 6 . A study of 2109 California insured women aged 40 to 69 years reported that among women making $100,000+ a year, only 8.2% did not have sex in the past year as compared with 49.5% of the women making $40,000 or less ( P < 0.001) 7 .…”
Section: Sexual Activity Rates Especially Low Among Low-income Peoplementioning
confidence: 99%
“…Sexual dysfunction refers to any condition that hinders a person's ability to derive satisfaction from sexual activity [ 9 ]. In particular, female sexual dysfunction (FSD) is a complex disorder with multi-faceted causes rooted in biological and psychosocial factors [ 11 ]. FSD can have detrimental effects on an individual’s self-esteem, sense of wholeness, and interpersonal relationships, often leading to emotional discomfort [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…11 Due to a lack of underwear, disposable pads, and washing facilities, women in rural areas unable to control urinary leakage, exposing them to poor hygiene and odor issues. 12 Various studies have linked increasing age, increasing parity, and lifting heavy objects to pelvic floor dysfunction. Furthermore, anatomical prolapse and, more importantly, older age at last delivery were linked to pelvic floor dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Due to a lack of underwear, disposable pads, and washing facilities, women in rural areas unable to control urinary leakage, exposing them to poor hygiene and odor issues. 12 …”
Section: Introductionmentioning
confidence: 99%